Who’s “in the room where it happens”? A taxonomy and five-step methodology for identifying and characterizing policy actors - Gracelyn Cruden; Erika L. Crable; Rebecca Lengnick-Hall; Jonathan Purtle (Implementation Science Communications, 2023)
Abstract Background Engaging policy actors in research design and execution is critical to increasing the practical relevance and real-world impact of policy-focused dissemination and implementation science. Identifying and selecting which policy actors to engage, particularly actors involved in “Big P” public policies such as laws, is distinct from traditional engaged research methods. This current study aimed to develop a transparent, structured method for iteratively identifying policy actors involved in key policy decisions—such as adopting evidence-based interventions at systems-scale—and to guide implementation study sampling and engagement approaches. A flexible policy actor taxonomy was developed to supplement existing methods and help identify policy developers, disseminators, implementers, enforcers, and influencers. Methods A five-step methodology for identifying policy actors to potentially engage in policy dissemination and implementation research was developed. Leveraging a recent federal policy as a case study—The Family First Prevention Services Act (FFPSA)—publicly available documentation (e.g., websites, reports) were searched, retrieved, and coded using content analysis to characterize the organizations and individual policy actors in the “room” during policy decisions. Results The five steps are as follows: (1) clarify the policy implementation phase(s) of interest, (2) identify relevant proverbial or actual policymaking “rooms,” (3) identify and characterize organizations in the room, (4) identify and characterize policy actors in the “room,” and (5) quantify (e.g., count actors across groups), summarize, and compare “rooms” to develop or select engagement approaches aligned with the “room” and actors. The use and outcomes of each step are exemplified through the FFPSA case study. Conclusions The pragmatic and transparent policy actor identification steps presented here can guide researchers’ methods for continuous sampling and successful policy actor engagement. Future work should explore the utility of the proposed methods for guiding selection and tailoring of engagement and implementation strategies (e.g., research-policy actor partnerships) to improve both “Big P” and “little p” (administrative guidelines, procedures) policymaking and implementation in global contexts.